Development of an online map of safe gun storage sites in Maryland for suicide prevention. (3rd October 2021) - Bongiorno, Diana M.; Kramer, Eric N.; Booty, Marisa D.; Crifasi, Cassandra K.
Abstract: Reducing access to lethal means of self-harm is a cornerstone of suicide prevention, and temporary, voluntary gun storage outside the home is one recommended approach. With the goal of facilitating access to gun storage outside the home in Maryland, we developed an online map of gun shops and law enforcement agencies willing to offer temporary, voluntary gun storage on a case-by-case basis. This project was modelled off of prior work by the Colorado Firearm Safety Coalition. As of July 2020, 32 gun shops and 3 law enforcement agencies agreed to be listed on our map. Others were hesitant to participate due to perceived legal and logistical barriers to temporary firearm storage. We demonstrate the feasibility of creating an online map that lists organisations offering temporary gun storage in Maryland. This brief report details our process, barriers encountered, and future considerations to improve access to offsite gun storage options.